Antibacterial activity of ethanol extract and fractions obtained from Taraxacum mongolicum flower - H. Qiao; T.J. Sun (Iranian Society of Pharmacognosy, 2014)
Background and objectives: Resistance towards reveling antibiotics has captured great interest in evaluating the antimicrobial properties of the natural plants. Taraxacum mongolicum is widely used as a folklore medicinal plant for its diuretic, antirheumatic and anti-inflammatory properties. Though there are some reports on antimicrobial properties of Taraxacum mongolicum, studies on antibacterial abilities of its flower are limited and it was decided to evaluate the antibacterial properties of the flowers in the present study. Methods: The antibacterial properties of ethanol extract of Taraxacum mongolicum flower, and its fractions (petroleum ether, ethyl acetate (ET), and aqueous fractions) were examined through agar disc diffusion method, and the minimum inhibitory concentration (MIC) was determined. Four Gram-negative and two Gram-positive bacteria were used in the study. Results: The antibacterial test results showed that the ET fraction strongly inhibited the growth of all of the microorganisms, especially Pseudomonas aeruginosa and Bacillus subtilis (with MIC values of 125 μg/mL and 62.5 μg/mL, respectively), whereas the ethanol extract and the other two fractions demonstrated moderate and weak activities, respectively. Conclusion: The ET fraction obtained from Taraxacum mongolicum flowers presented high antibacterial activity and might be suggested for use as a natural preservative ingredient in pharmaceutical industries.